Development of Digitalization of The “MP Digilib” Library System for Improvement of Academic Services - Setiawan, Aditya Chandra; Haq, Mohammad Syahidul; Khamidi, Amrozi; Putri, Adinda Rahma; Iswahyuni, Dewi Laras (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
Abstract: This study aims to describe the condition of the 'Taman Baca' service of the Department of Education Management before and during the covid-19 pandemic; designing online 'Taman Baca' access service that is the application "MP DigiLib" according to the needs of students, lecturers, educational personnel and the community; and know the level of student satisfaction with academic services. The method used in the development of the 'Taman Baca' service is to use the Waterfall Model, which is to apply 2 stages of 5 stages, among others Analysis and Design to design digital library applications. The result obtained is the realization of the digitization of the library by using the SLiMS platform in the localhost version and there are two page views available, namely pages for visitors and pages for the manager of "MP DigiLib"; and the improvement of student satisfaction with academic services, especially in the tangibles aspect where there are library services that have been digitized.  Keywords: Increased, Services, Digitization, Library Systems